Biosecurity risks associated with vaccine platform technologies. Issue 17 (14th April 2022) - Sandbrink, Jonas B.; Koblentz, Gregory D.
Highlights: Vaccine platforms are very valuable for rapidly tackling emerging pathogens. Work on virally vectored vaccines may exhibit relatively high dual-use risk. Especially worrying is work to circumvent pre-existing anti-vector immunity. Dual-use risks may be reduced by using non-human vectors or novel RNA technology. Researchers working on viral vectors need to become aware of dual-use risks. Abstract: Vaccine platforms have been critical for accelerating the timeline of COVID-19 vaccine development. Faster vaccine timelines demand further development of these technologies. Currently investigated platform approaches include virally vectored and RNA-based vaccines, as well as DNA vaccines and recombinant protein expression system platforms, each featuring different advantages and challenges. Viral vector-based and DNA vaccines in particular have received a large share of research funding to date. Platform vaccine technologies may feature dual-use potential through informing or enabling pathogen engineering, which may raise the risk for the occurrence of deliberate, anthropogenic biological events. Research on virally vectored vaccines exhibits relatively high dual-use potential for two reasons. First, development of virally vectored vaccines may generate insights of particular dual-use concern such as techniques for circumventing pre-existing anti-vector immunity. Second, while the amount of work on viral vectors for gene therapy exceeds that for vaccine research, work on virally vectored vaccines may increase the number of individuals capable of engineering viruses of particular concern, such as ones closely related to smallpox. Other platform vaccine approaches, such as RNA vaccines, feature relatively little dual-use potential. The biosecurity risk associated with platform advancement may be minimised by focusing preferentially on circumventing anti-vector immunity with non-genetic rather than genetic modifications, using vectors that are not based on viruses pathogenic to humans, or preferential investment into promising RNA-based vaccine approaches. To reduce the risk of anthropogenic pandemics, structures for the governance of biotechnology and life science research with dual-use potential need to be reworked. Scientists outside of the pathogen research community, for instance those who work on viral vectors or oncolytic viruses, need to become more aware of the dual-use risks associated with their research. Both public and private research-funding bodies need to prioritise the evaluation and reduction of biosecurity risks.